Disappointment: House of Cards - Shushma Raj Choudhary (IJRDO - Journal of Social Science and Humanities Research, 2026)
House of cards by Sudha Murthy is a poignant reflection on how ambition, greed, and materialism can erode the foundation of a marriage. The novel critiques patriarchal control and financial secrecy, ultimately emphasizing that a family life built on status and wealth is fragile and unsustainable.